Mutations in the Glycosyltransferase Domain of GLT8D1 Are Associated with Familial Amyotrophic Lateral Sclerosis - Hardiman, Orla (My University, 2019)
Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disorder without effective neuroprotective therapy. Known genetic variants impair pathways, including RNA processing, axonal transport, and protein homeostasis. We report ALS-causing mutations within the gene encoding the glycosyltransferase GLT8D1. Exome sequencing in an autosomal-dominant ALS pedigree identified p.R92C mutations in GLT8D1, which co-segregate with disease. Sequencing of local and international cohorts demonstrated significant ALS association in the same exon, including additional rare deleterious mutations in conserved amino acids. Mutations are associated with the substrate binding site, and both R92C and G78W changes impair GLT8D1 enzyme activity. Mutated GLT8D1 exhibits in vitro cytotoxicity and induces motor deficits in zebrafish consistent with ALS. Relative toxicity of mutations in model systems mirrors clinical severity. In conclusion, we have linked ALS pathophysiology to inherited mutations that diminish the activity of a glycosyltransferase enzyme.
Keywords: Amyotrophic lateral sclerosis (ALS); Genetic variants; RNA processing; Axonal transport; Protein homeostasis; Exome sequencing; Autosomal-dominant ALS pedigree; Exon; Enzyme activity; Cytotoxicity; Zebrafish; Glycosyltransferase GLT8D1